Pengaruh Pendidikan Kewarganegaraan terhadap Kesadaran Perlindungan Data Pribadi Mahasiswa di Ruang Digital: The Influence of Citizenship Education on Students' Personal Data Protection Awareness in the Digital Space - Intan Noraziza Making (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
Abstract: Civic education not only serves to strengthen national identity but also functions as a means of shaping citizens’ ethics and responsibility in the digital era. Therefore, integrating civic values into the digital curriculum is an important step toward fostering a culture of personal data protection among university students. This study aims to analyze the influence of civic education on students’ awareness of personal data protection in the digital space. The growing intensity of students’ online activities has made personal data increasingly vulnerable to misuse, while privacy awareness remains relatively low. Civic education is considered to play a strategic role in fostering values of responsibility, ethics, and understanding of citizens’ rights and obligations, including in the digital context. The research employed a qualitative method with a descriptive approach. Data were collected through interviews, focus group discussions, and document analysis, and then examined using thematic analysis techniques. The research subjects were active university students from various faculties who had completed the civic education course and actively used digital platforms. The findings reveal that civic education has a positive influence on students’ awareness of personal data protection. Digital literacy serves as the main mediating factor that strengthens this relationship, while digital social norms also have an effect, although to a lesser extent. Furthermore, differences were found in the level of awareness between students from technology-related and non-technology-related majors. Overall, this study emphasizes that data privacy issues should be integrated into the civic education curriculum to cultivate a generation of students who are critical, aware, and responsible in protecting their personal data in the digital era.